PENGARUH MODEL PQ4R PADA KEMAMPUAN MEMBACA PEMAHAMAN - Lukman; Herwandi (Jurnal Pendidikan dan Pembelajaran, 2023)
The purpose to be achieved in this research is to examine and review the reading comprehension ability before using the Preview, Question, Read, Reflect, Recite and Review (PQ4R) model of Class VIII students of SMP Negeri 2 Bantaeng, reading comprehension ability after using the Preview, Question, Read, Reflect, Recite and Review (PQ4R) model of Class VIII students of SMP Negeri 2 Bantaeng and prove the use of the Preview, Question, Read, Reflect, Recite and Review (PQ4R) model on the reading comprehension ability of Class VIII students.This type of research is quantitative pre-experiment because the data obtained in the form of numbers from the results of student work. Data collection techniques in this study were carried out by means of observation, test and documentation techniques. The data collection technique of the PQ4R model in this study was carried out by giving multiple choice tests before and after treatment using the PQ4R model. The analysis technique that has been collected in the form of test results, then analyzed to determine the ability of students in reading comprehension before and after using the PQ4R model. Based on the results of research on the effect of using the PQ4R model on reading comprehension skills, it can be concluded that the PQ4R model has a significant effect on the reading comprehension skills of students VIII SMP Negeri 2 Bantaeng. This can be seen in the results of the initial test and the final test of students' reading comprehension skills. Based on the test results obtained before using the PQ4R model students still look less, showing the maximum value is 80 already included in the category of completion. However, the minimum score is still not complete, which is 35. The average acquisition of all student scores is 55. For the test results there are 21 students who are still in the very low category, 3 students who are still in the low category, and there are only 3 students who are complete. Based on the test results obtained after using the PQ4R model, the maximum score of 90 is included in the complete category. The average acquisition of the overall student score decreased from the average test result of 80. The application of the PQ4R model has at least had an influence on student scores which in the initial test only 3 students were complete, while the final test can make all students complete in answering questions according to the material provided, in this case there are still students who are still in the range of values in the low value category. Based on the results of the inferential statistical analysis, the mann-whitney analysis on Asymp. Sig. (2-tailed) analysis results in a significant value of 0.000 less than the significant value of 0.05. Based on the results of inferential statistics on the mann-whitney test, it can be concluded that Ho is rejected and H1 is accepted, namely there is a significant effect of the PQ4R model on the learning outcomes of reading comprehension of Class VIII SMP Negeri 2 Bantaeng.